Comparative slope analysis by methods of slices and finite element analysis - Choo, Glen Ming Liang. (2013)
Slope stability studies are conducted to provide an economical and safe design of embankment, landfill and excavation. There are basically two main methods namely LEM (Limit Equilibrium Method) and FEM (Finite Element Method) which can be used to analyze slope stability problems in real life. The conventional LEM which includes Ordinary Method of Slice, Bishop’s Simplified Method and Spencer Method is commonly used in geotechnical engineering when calculating FOS (Factor of Safety) in slope analysis. As technology gets more sophisticated, more advanced finite element soil analyzing programs were introduced and slowly gaining popularity in geotechnical field over the past decades.